Utilization of Close Circuit Television (CCTV) in Preventing Traffic Jams by the Ciamis Police Traffic Unit - Wijaya, Sandy (Advances in Police Science Research Journal, 2024)
The Jurisdiction of Ciamis Resort Police Force has one of the most complex traffic troubles including traffic jam, bottleneck and high density traffic. The main reason is because Ciamis is dominated by main road between West and Central Java and also bypassed tourist attraction such as Pangandaran Beach and Green Canyon. Ciamis Resort Police especially the Traffic Division innovate by building a Traffic Management Centre that can overseer some troublespot with high density traffic. This was done to overseer the traffic density and therefore could prevent traffic jam. The main reason behind this research is to determine how traffic division utilize the technology of Close Circuit Television so it could be used to prevent traffic jam before it were to happen, this research includes: 1. General description of the traffic situation inside the jurisdiction of Ciamis Resort Police Force. 2. The factors that influence the usage of Close Circuit Television 3. The ideal use of Close Circuit Television by the Traffic Division to prevent traffic jam. The theory that was used in this research is the public administration theory of POSDCoRB that was invented by Luther Hasley Gullick, the analysist technique of SWOT and the concept of CCTV and the concept of utilization. The research use qualitative approach with field research methods and use interview, observation and document study to excavate data. The research results shows that the utilization of CCTV by the Traffic Division in Ciamis Resort Police Force can prevent traffic jam in some troublespot that already overseered by CCTV. But the vast territory of the jurisdiction of Ciamis Resort Police Force that includes 2 districts cannot be fully covered. The lack of unit member, low resources and members that has specified CCTV skills become the main problem that obstruct the utilization of CCTV. Hence, the utilization of CCTV must be supported by adding more members of Ciamis Resort Police Force and resources support both financially and skill utilization.